Phytotoxic effects of fungicides, insecticides and nonpesticidal components on pepper depending on water quality - Vuković, Slavica M; Inđić, Dušanka V; Gvozdenac, Sonja M (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
Modern agriculture relies on simultaneous application of fungicides, insecticides, fertilizers and adjuvants. The selection of compounds for tank-mixes has been rarely studied and it presents a risk in the application of pesticides but the quality of water should also be considered. The aim of this study was to assess the phytotoxic effects of several fungicides, insecticides, a complex fertilizer, an adjuvant and their mixtures on pepper (Capsicum annuum L.) as a test plant, depending on water quality. The effects of the pesticides: azoxystrobin (Quadris, 0.75 l/ha), mancozeb (Dithane M-70, 2.5 kg/ha), thiamethoxam (Actara 25-WG, 0.07 kg/ha) and cypermethrin (Cipkord EC-20, 0.3 l/ha), a complex fertilizer (Mortonijc plus /hereinafter: M+/ 3kg/ha), an adjuvant (Sillwet 77-L, 0.1 l/ha) and their mixtures, were assessed depending on the quality of water (well water slightly alkaline, very hard and with high nitrite content; tap water – neutral and slightly hard; surface water – alkaline, slightly hard and with high content of nitrite and ammonia) using a puncture method. The effects were assessed after seven days by measuring the diameter of chlorosis and/or necrosis around puncture sites, and were expressed in mm2. The significance of differences between treatments was analyzed using a one-way ANOVA (LSD 0.05 %). In the slightly alkaline and very hard well water, all spray liquids containing Dithane M-70 caused a significant increase in leaf chlorosis area (from 6.0 to 25.2 mm2), compared to the control and other treatments. In the neutral and slightly hard tap water, all spray liquids containing Dithane M-70 caused a significant increase in leaf chlorosis (5.3 to 7.9 mm2) compared to the control and the other spray liquids, although its phytotoxicity in that water was at a lower level than it was in well water. However, in the weakly alkaline and slightly hard surface water from the river Sava, Dithane M–70, Dithane M-70 + Actara WG-25, Dithane M-70 + Sillwet L-77, and Dithane M-70 + Actara 25-WG + M+ showed a significant increase in phytotoxicity, compared to the control.
Keywords: Pesticides; Water quality; Phytotoxicity